A Novel Unified Architecture for Public-Key Cryptography - Cilardo, A.; Mazzeo, A.; Mazzocca, N.; Romano, L. (Design, Automation and Test in Europe, 2005)
In this paper we propose a fully-parallel, bit-sliced unified architecture designed to perform modular multipication/exponentiation and GF(2^M) multiplication as the core operations of RSA and EC cryptography. The architecture uses radix-2 Montgomery technique for modular arithmetic, and a radix-4 MSD-first approach for GF(2^M) multiplication. To the best of our knowledge, it is the first unified proposal based on such a hybrid approach. The architecture structure is bit-sliced and is highly regular, modular, and scalable, as virtually any datapath length can be obtained at a linear cost in terms of hardware resources and no costs in terms of critical path. Our proposal outperforms all similar unified architectures found in the technical literature in terms of clock count and critical path. The architecture has been implemented on a Field-Programmable Gate Array (FPGA) device. A highly compact and efficient design was obtained taking advantage of the architectural characteristics.